A self-hygroscopic resin and desiccant and preparation method thereof

Through the polymerization reaction of acrylamide and alkali metal salts, the network structure resin is generated and combined with sesapite powder, which solves the problem of insufficient hygroscopicity of highly absorbent resins in the air, and achieves efficient moisture absorption and latching, which improves the Hygroscopic properties of desiccant.

CN114181346BActive Publication Date: 2025-01-07SUPER DRY DESICCANT SHENZHEN
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111474637.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-06
Publication Date
2025-01-07
Estimated Expiration
2041-12-06

AI Technical Summary

Technical Problem

The existing highly absorbent resins have insufficient hygroscopicity in the air, and cannot effectively exert water storage capacity, and cannot meet the needs of high-performance hygroscopic materials.

Method used

Acrylamide is used to polymerize with alkali metal or alkaline earth metal salts under the action of initiator and crosslinking agent to form an autonomous hygroscopic resin with a network branch structure, and is compounded with sesapoleite powder to improve the hygroscopic properties of the resin.

Benefits of technology

The moisture absorption rate of resin in the air is significantly improved, and the water lock rate and moisture absorption rate are both improved. The resin has good stability after water absorption is saturated, and it is not easy to release moisture. The moisture absorption performance of desiccant is also greatly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure BDA0003393074090000071
    Figure BDA0003393074090000071
  • Figure BDA0003393074090000072
    Figure BDA0003393074090000072
Patent Text Reader

Abstract

The present application relates to the technical field of desiccants, and specifically discloses a self-hygroscopic resin and a desiccant and a preparation method thereof. A self-hygroscopic resin, the preparation method of which is: adding acrylamide to a metal salt solution, then adding an initiator and a cross-linking agent, performing a polymerization reaction under stirring to obtain a reactant, drying the reactant to obtain a self-hygroscopic resin; the metal salt solution is an alkali metal salt solution or an alkaline earth metal salt solution; the molar ratio of acrylamide to the metal salt is 1: (0.7-5), the hygroscopicity of the resin reaches 798-1308%, and the hygroscopicity of the resin is excellent. The self-hygroscopic resin of the present application is coated with sepiolite powder to obtain a desiccant, the hygroscopicity of the desiccant reaches 1626-1684%, the hygroscopicity of the desiccant is excellent, and it is used in industries such as shipping, and can absorb water vapor in a closed space well.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of desiccants, and more specifically, to a self-hygroscopic resin and desiccant and a preparation method thereof. Background Art

[0002] Desiccant is mainly made of substances that can extract and absorb moisture. Commonly used substances for moisture absorption are organic polymer hygroscopic materials, inorganic salts and mineral materials. Although inorganic salts and mineral materials absorb moisture quickly, their moisture absorption capacity is not high, and inorganic salts are easy to deliquesce and have poor stability. Polymer hygroscopic materials are generally highly absorbent resins, which have good comprehensive moisture absorption properties.

[0003] At present, most of the super absorbent resins on the market are "hydroponic type", and the moisture absorption rate in water can reach 1000% or more, but the active absorption of water vapor at room temperature is very weak, and almost no active absorption of water vapor in the air. Therefore, although its theoretical water absorption rate is very high, its moisture absorption rate is slow and its moisture absorption capacity is small. When used in logistics freight warehousing, super absorbent resins cannot exert their excellent water storage capacity and cannot meet people's needs for high-performance hygroscopic materials.

[0004] With respect to the related art, the applicant believes that how to improve the hygroscopicity of water-absorbent resin in the air to obtain highly water-absorbent polymer resin and desiccant is a problem to be solved urgently. Summary of the invention

[0005] In order to improve the hygroscopicity of a polymer water-absorbing resin in the air, the present application provides an autonomous hygroscopic resin and a desiccant and a preparation method thereof.

[0006] In the first aspect, the present application provides an autonomous hygroscopic resin, which adopts the following technical solution:

[0007] A self-hygroscopic resin, the preparation method of which is:

[0008] Add acrylamide to a metal salt solution, then add an initiator and a cross-linking agent, perform a polymerization reaction under stirring to obtain a reactant, and dry the reactant to obtain an autonomous hygroscopic resin;

[0009] The metal salt solution is an alkali metal salt solution or an alkaline earth metal salt solution;

[0010] The molar ratio of the acrylamide to the metal salt is 1:(0.7-5).

[0011] By adopting the above technical scheme, under the action of an initiator and a cross-linking agent, acrylamide and an alkali metal salt solution or an alkaline earth metal salt solution undergo a polymerization reaction, and the generated product is a polymer with a network branching structure, has a spatial three-dimensional structure with a large capacity, and is insoluble in water. The network structure unfolded after moisture absorption is stable and belongs to an elastic glass body.

[0012] The resin of the present application can achieve a water lock rate of 95.18% in 24 hours, 83.78% in 72 hours, 67.08% in 120 hours, and 57.96% in 168 hours. After the resin reaches the water absorption saturation state, it is not easy to release water due to a decrease in ambient humidity or an increase in ambient temperature, which is beneficial to improving the hygroscopic stability of the resin. The resin of the present application can achieve a moisture absorption rate of 1308% in RH90% air, which may be because calcium chloride or lithium chloride participates in the polymerization of acrylamide, and the generated resin can automatically absorb water vapor in the air and can autonomously lock water in its own structure, thereby greatly improving the moisture absorption rate of the resin in the air.

[0013] The resin of the present application gradually changes from an opaque solid to a transparent gel during the moisture absorption process, and does not produce a liquid state during the moisture absorption process. In practical applications, the degree of moisture absorption of the resin can be determined based on the transparency of the resin.

[0014] Preferably, the alkaline earth metal salt solution is a calcium chloride solution, and the molar ratio of acrylamide to calcium chloride is 1:(1-3.5).

[0015] Preferably, the concentration of the calcium chloride solution is 1-5 mol / L.

[0016] Preferably, the alkali metal salt solution is a lithium chloride solution, and the molar ratio of acrylamide to lithium chloride is 1:(1-3).

[0017] Preferably, the concentration of the lithium chloride solution is 1-7 mol / L.

[0018] By adopting the above technical scheme, the alkaline earth metal salt solution can be a salt solution of beryllium, magnesium, calcium, strontium, barium, etc., preferably a calcium chloride solution; the alkali metal salt solution can be a salt solution of lithium, sodium, potassium, rubidium, cesium, etc., preferably a lithium chloride solution.

[0019] Optimizing the ratio of acrylamide to calcium chloride or lithium chloride, and further optimizing the molecular structure of the polymerization product, further expands the three-dimensional space capacity of the polymerization product, which is beneficial to improving the moisture absorption rate of the resin.

[0020] After limiting the molar ratio of acrylamide to calcium chloride or lithium chloride, the concentration of the calcium chloride or lithium chloride solution is further limited. As the concentration of the calcium chloride or lithium chloride solution increases, the rate of the polymerization reaction accelerates, and the water locking rate and moisture absorption rate of the polymerized resin also increase with the increase of the calcium chloride or lithium chloride concentration. However, when the concentration of the calcium chloride solution increases to 5 mol / L and the concentration of the lithium chloride solution increases to 7 mol / L, the increase in the moisture absorption rate is not obvious, and there is even a downward trend. The concentrations of the calcium chloride and lithium chloride solutions are limited to ensure that the resin can achieve a better moisture absorption effect.

[0021] Preferably, the temperature of the drying operation is 70-80°C and the drying time is 23-25h.

[0022] Preferably, the initiator is potassium persulfate, and the cross-linking agent is NN methylenebisacrylamide.

[0023] By adopting the above technical solution, potassium persulfate has particularly good stability due to its high purity. NN methylenebisacrylamide is used as a high-efficiency cross-linking agent in combination with potassium persulfate to promote the polymerization of acrylamide and calcium chloride or lithium chloride. The polymerized product is dried at an appropriate temperature, and the drying temperature can be any temperature between 70-80°C, and the drying time is controlled, and the drying time can be any time between 23-25h. For example, the drying temperature is 70°C and the drying time is 25h; or the drying temperature is 80°C and the drying time is 23h, to obtain a stable resin.

[0024] In a second aspect, the present application provides a desiccant, which adopts the following technical solution:

[0025] A desiccant comprises any one of the above self-hygroscopic resins and sepiolite powder, wherein the weight ratio of the self-hygroscopic resin to the sepiolite powder is 1:(1-2).

[0026] By adopting the above technical solution, the pore specific surface area of ​​sepiolite powder is high, and it has strong adsorption, and can absorb liquid and gas. Self-hygroscopic resin is a polymer material with a small specific surface area. Wrapping sepiolite powder outside the resin can increase the roughness of the resin surface and relatively increase the specific surface area of ​​the resin, thereby increasing the contact area between the desiccant and the moisture in the air. In addition, the water vapor absorbed by the sepiolite powder through physical adsorption can be transferred to the resin, thereby improving the hygroscopic performance of the desiccant.

[0027] Preferably, the sepiolite powder is modified sepiolite powder, and the modification method thereof is:

[0028] The sepiolite powder was modified by using a mixed solution of silane coupling agent and sodium polyacrylate.

[0029] By adopting the above technical scheme, the sepiolite powder itself has a certain viscosity, and the silane coupling agent and sodium polyacrylate are wrapped on the surface of the sepiolite powder, which improves the dispersion performance of the sepiolite powder, prevents flocculation and agglomeration between the sepiolite powder particles, and makes the sepiolite powder evenly distributed on the resin surface, which is beneficial to improving the moisture absorption effect of the resin; at the same time, it can also improve the bonding strength between the sepiolite powder and the resin, reduce the probability of the sepiolite powder falling off the resin, and ensure the stability of the desiccant product.

[0030] In a second aspect, the present application provides a desiccant, which adopts the following technical solution:

[0031] A method for preparing a desiccant comprises the following steps:

[0032] S1. Soak the self-hygroscopic resin in deionized water to absorb water and swell:

[0033] S2. After the swelling of the self-hygroscopic resin, the surface moisture is dried and blended with sepiolite powder, so that the sepiolite powder is wrapped in the surface of the self-hygroscopic resin to obtain composite particles;

[0034] S3. The composite particles are placed in an environment of 23±2°C and RH less than 70% for 1.5-2.5 hours, and then dried, and the sepiolite powder falling off the surface of the composite particles is sieved out to obtain a desiccant.

[0035] By adopting the above technical solution, the resin can absorb the sepiolite powder well after swelling. After the resin absorbs the sepiolite powder, it is left to stand for a period of time, so that the sepiolite powder can be better bonded to the resin.

[0036] In summary, this application has the following beneficial effects:

[0037] 1. Since the present application adopts calcium chloride or lithium chloride to polymerize with acrylamide, the moisture absorption rate of the synthesized resin reaches 798-1308%, the 24h water locking rate can reach 93.1-95.18%, the 72h water locking rate can reach 80.5-83.78%, the 120h water locking rate can reach 62.70-67.08%, and the 168h water locking rate can reach 52.90-57.96%. The hygroscopic performance of the resin is excellent.

[0038] 2. In the present application, the desiccant is preferably prepared by wrapping the modified sepiolite powder outside the resin. The prepared desiccant has a moisture absorption rate of 1626-1684% and an average moisture absorption rate of 3.12-3.17 mg / (g·min), and the desiccant has excellent moisture absorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Attached Figure 1 Infrared spectrum of the self-hygroscopic resin in Example 6 of the present application.

[0040] raw material

[0041] The degree of polymerization of sodium polyacrylate is 10;

[0042] The silane coupling agent used is KH-560.

[0043] Preparation Example

[0044] Preparation Example 1

[0045] Modified sepiolite powder, the preparation method thereof is as follows:

[0046] 1) 5 kg of silane coupling agent and 2 kg of sodium polyacrylate were mixed evenly to obtain a modified mixed solution;

[0047] 2) adding the modified mixed solution into water to prepare a treatment solution with a mass concentration of 2%;

[0048] 3) stirring the sepiolite powder at a speed of 500 r / min, and at the same time, spraying the treatment liquid on the surface of the sepiolite powder by ultrasonic atomization, the weight ratio of the sepiolite powder to the treatment liquid is 1:80, the treatment liquid is sprayed within 10 minutes, and then the stirring speed is increased to 1000 r / min, stirring for 30 minutes; and then drying at 150° C. for 30 minutes to obtain modified sepiolite powder.

[0049] Preparation Example 2

[0050] The difference from Preparation Example 1 is that in Preparation Example 2, 7 kg of silane coupling agent is added into water to prepare a treatment liquid with a mass concentration of 2%, and the other steps are the same as those in Preparation Example 1.

[0051] Preparation Example 3

[0052] The difference from Preparation Example 1 is that in Preparation Example 2, 7 kg of sodium polyacrylate is added into water to prepare a treatment solution with a mass concentration of 2%, and the other steps are the same as those in Preparation Example 1. DETAILED DESCRIPTION

[0053] The present application is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0054] Example

[0055] Example 1

[0056] The self-hygroscopic resin is prepared by:

[0057] According to the ratio in Table 1, weigh the alkaline earth metal salt calcium chloride, dissolve the calcium chloride in water, and prepare a calcium chloride solution with a concentration of 1 mol / L; mix the calcium chloride solution, acrylamide, initiator potassium persulfate, and cross-linking agent NN methylenebisacrylamide evenly, stir until all the solutes are dissolved in the solvent, and continue stirring until an exothermic reaction begins, stop stirring, and continue the reaction until the temperature drops to 25°C to obtain a reaction product, grind the reaction product, and place it in a 75°C environment for drying for 24 hours to obtain an autonomous hygroscopic resin.

[0058] Embodiment 2-5

[0059] Different from Example 1, the ratios of the reaction raw materials in Examples 2-5 are different, see Table 1 for details.

[0060] Embodiment 6-10

[0061] Different from Example 1, the alkaline earth metal salt calcium chloride in Examples 6-10 is replaced by alkali metal lithium chloride. The raw material ratios are shown in Table 1.

[0062] Table 1 Raw material ratio table in Example 1-10 (0.1kg)

[0063] Acrylamide Calcium chloride Lithium chloride Potassium Persulfate NN Methylene Bisacrylamide Example 1 71 77.7 0 2.025 0.770 Example 2 71 111.0 0 2.835 2.310 Example 3 71 222.0 0 3.375 3.850 Example 4 71 388.5 0 6.885 4.620 Example 5 71 555.0 0 9.450 5.390 Example 6 71 0 29.4 8.100 4.620 Example 7 71 0 42.0 9.450 5.390 Example 8 71 0 71.4 11.340 6.468 Example 9 71 0 126.0 12.150 6.930 Example 10 71 0 210.0 13.500 7.700

[0064] The self-hygroscopic resin in Example 6 was subjected to component analysis and infrared spectrum detection. The component analysis results are shown in Table 2 and the infrared spectrum is shown in Table 2. Figure 1 .

[0065] Table 2 Component analysis

[0066] Serial number Component name content(%) 1 Polyacrylamide 80.0 2 water 16.0 3 Lithium chloride 3.9

[0067] In the infrared spectrum of standard polyacrylamide, 3416cm -1 Free -NH 2 The characteristic absorption peak of -1 The place is associated with -NH 2 The characteristic absorption peak is 2926cm -1 The characteristic absorption peak of methylene antisymmetric stretching vibration is 2855cm -1 The characteristic absorption peak of the methylene symmetric stretching vibration is 1655cm -1 The carbonyl characteristic absorption peak is at 1620cm -1 The characteristic absorption peak of NH bending vibration is 1561cm -1 The NH bending vibration of secondary amide is at 1453 cm -1 The characteristic absorption peak of methylene deformation is 1174cm -1 and 1119cm -1The absorption peak at is related to the CN stretching vibration. ("Infrared Spectrum Analysis of Polyacrylamide", Chen Hesheng, Shao Jingchang, Analytical Instruments, Issue 3, 2011).

[0068] Combine Table 2 with Figure 1 Analysis shows that in the infrared spectrum of the self-hygroscopic resin synthesized in this application, 3378 cm -1 -NH 2 The characteristic absorption peak is 1645cm -1 The carbonyl characteristic absorption peak is at 1455cm, corresponding to the stretching vibration of C=O. -1 The characteristic absorption peak of methylene deformation is 1180cm -1 and 1117cm -1 The absorption peak at is related to the CN stretching vibration.

[0069] Compared with standard polyacrylamide, the self-hygroscopic resin-NH 2 The characteristic absorption peak of free -NH 2 The characteristic absorption peak of -NH 2 This may be due to the presence of chloride ions and -NH 2 N connection on the NH 2 The electron cloud of -NH 2 Similarly, the characteristic absorption peak of C=O may shift slightly because the metal ion is connected to the O on C=O, affecting the electron cloud of C=O; the chloride ion and -NH 2 The N on the C=O is connected, and the metal ion is connected with the O on the C=O to form a stable ring structure. Under the combined effect of the electron cloud and the steric hindrance, the stretching vibration of the methylene group and the bending vibration of the NH are suppressed, resulting in the disappearance of the characteristic absorption peaks of the methylene stretching vibration and the NH bending vibration, which also confirms the molecular structure of the autonomous hygroscopic resin of the present application.

[0070] Examples 11-14

[0071] Different from Example 3, the concentrations of calcium chloride solutions in Examples 11-14 are different, see Table 3 for details.

[0072] Table 3 Calcium chloride solution concentration table in Example 3 and Examples 11-14 (mol / L)

[0073] Example 3 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Calcium chloride solution concentration 1 3 5 0.5 8

[0074] Examples 15-18

[0075] Different from Example 8, the concentrations of the lithium chloride solutions in Examples 15-18 are different, as shown in Table 4.

[0076] Table 4 Lithium chloride solution concentration in Example 8 and Examples 15-18 (mol / L)

[0077] Example 8 Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Calcium chloride solution concentration 1 4 7 0.5 10

[0078] Comparative Example

[0079] Comparative Example 1

[0080] Polyacrylamide resin, the preparation method thereof is as follows:

[0081] 7.1 kg of acrylamide was dissolved in water, and then nitrogen was passed through for 5 minutes to remove dissolved oxygen. When heated to 60°C, 0.2 kg of potassium persulfate initiator and 0.07 kg of N-N-methylenebisacrylamide cross-linking agent were added, and the reaction was carried out for 4 hours. Then, the heating was stopped and the reaction was allowed to stand for 3 hours to obtain a reaction product. The reaction product was crushed and dried in an environment of 75°C for 24 hours to obtain a polyacrylamide resin.

[0082] Comparative Example 2

[0083] Different from Example 1, the amount of calcium chloride in Comparative Example 2 is 2.44 kg.

[0084] Comparative Example 3

[0085] Different from Example 1, the amount of calcium chloride in Comparative Example 3 is 77.7 kg.

[0086] Comparative Example 4

[0087] Different from Example 6, the amount of lithium chloride in Comparative Example 4 is 0.68 kg.

[0088] Comparative Example 5

[0089] Different from Example 6, the lithium chloride in Comparative Example 4 is 33.6 kg.

[0090] Performance testing

[0091] Detection Methods

[0092] The moisture absorption rate and water locking rate of the resins prepared in Examples 1-18 and Comparative Examples 1-5 were measured, and the test results are shown in Table 5.

[0093] Water absorption rate determination: soak 5g of resin in water, weigh and record the weight once a day until the weight of the resin no longer increases, and then calculate the water absorption rate, water absorption rate = (final weight - initial weight) / initial weight × 100%.

[0094] Determination of moisture absorption rate: 5 g of resin was placed in an environment of 35°C and 90% RH, and the weight was recorded once a day until the weight of the resin stopped increasing. Then the moisture absorption rate was calculated. Moisture absorption rate = (final weight - initial weight) / initial weight × 100%.

[0095] Determination of water lock rate: After the resin is saturated with water, its weight is recorded as M0. Put the saturated resin into a beaker, weigh the total weight of the saturated water-absorbing resin and the beaker as M1, place the beaker in a 25°C environment, and measure the mass of the resin and the beaker after 24h, 72h, 120h, and 168h as M2 to calculate the water lock rate.

[0096]

[0097] Table 5 Performance test results of Examples 1-18 and Comparative Examples 1-5

[0098]

[0099]

[0100] Combining Examples 1-18 with Comparative Examples 1-5, and Table 5, it can be seen that the water absorption rate of the resin of Comparative Examples 1-5 can reach 895%, but the moisture absorption rate in the air is greatly reduced, while the water absorption rate, moisture absorption rate, and water lock rate of the resin prepared in Examples 1-18 of the present application are all higher than those of Comparative Examples 1-5. This may be because the resin prepared in the present application can actively absorb moisture, and the effect of moisture absorption performance in the air is better, and compared with Comparative Examples 1-5, the hygroscopicity of the resin of the present application in the air is significantly improved.

[0101] Combining Example 1 with Comparative Example 1 and Table 5, it can be seen that the moisture absorption rate of the resin prepared in Example 1 is much higher than that in Comparative Example 1. This may be because the polymer in Comparative Example 1 is formed by polymerization of acrylamide monomers, and calcium chloride in Example 1 also participates in the polymerization reaction as part of the polymerization monomer. Cationic exchange occurs during the polymerization reaction, and the cations are coordinated and connected to acrylamide to obtain a polymer product with a multi-chain spatial structure, which enhances the hygroscopicity and water-locking ability of the resin.

[0102] In combination with Example 1 and Comparative Examples 2-3, and in combination with Table 5, it can be seen that compared to Example 1, the hygroscopicity and water lock rate of the resin obtained in Comparative Examples 2-3 are significantly reduced, wherein the hygroscopicity and water lock rate of the resin in Comparative Example 2 are lower. This may be due to the fact that the amount of calcium chloride used in Comparative Example 2 is too little, so that calcium chloride cannot participate in the polymerization reaction as a polymerization monomer but promotes the polymerization of acrylamide monomer as an additive, and there is no coordination metal on the polymerized product, and its hygroscopicity is similar to simple acrylamide polymerization. And the amount of calcium chloride used in Comparative Example 3 is too high, which may change the structure of the polymer finally formed or affect the progress of the polymerization reaction, causing the hygroscopicity of its polymerized product to decrease. Therefore, the hygroscopicity of the resin obtained within the ratio range of acrylamide and calcium chloride in the present application is more excellent. Similarly, in combination with Example 6 and Comparative Examples 4-5, it can be concluded that the hygroscopicity of the resin obtained within the ratio range of acrylamide and lithium chloride in the present application is more excellent.

[0103] It can be seen from Examples 1-5 and Table 5 that the ratio of acrylamide to calcium chloride affects the hygroscopic properties of the resin, and the ratio of acrylamide to calcium chloride in Example 3 is optimal.

[0104] It can be seen from Examples 6-10 and Table 5 that the ratio of acrylamide to lithium chloride affects the hygroscopic properties of the resin, and the ratio of acrylamide to lithium chloride in Example 8 is optimal.

[0105] Combining Example 3 with Examples 11-14 and Table 5, it can be seen that when the ratio of acrylamide to calcium chloride is determined, as the concentration of calcium chloride increases, the hygroscopicity of the obtained resin gradually increases, but when the concentration of calcium chloride exceeds 5 mol / L, the hygroscopicity of the resin decreases. Within the range of calcium chloride concentration in the present application, the hygroscopicity of the obtained resin can achieve a better effect.

[0106] Combining Example 8 with Examples 15-18 and Table 5, it can be seen that when the ratio of acrylamide to lithium chloride is determined, as the concentration of lithium chloride increases, the hygroscopicity of the obtained resin gradually increases, but when the concentration of lithium chloride exceeds 7 mol / L, the hygroscopicity of the resin decreases. Within the lithium chloride concentration range of the present application, the hygroscopicity of the obtained resin can achieve a better effect.

[0107] Application Examples

[0108] Application Example 1

[0109] A desiccant, the preparation method of which is as follows:

[0110] S1. Soak 1 kg of the autonomous hygroscopic resin obtained in Example 1 in deionized water for 2 h to allow the autonomous hygroscopic resin to absorb water and swell:

[0111] S2. After the swelling of the self-hygroscopic resin, the surface moisture was dried and blended with 30kg of sepiolite powder, and the blending time was 5min, so that the sepiolite powder was wrapped in the surface of the self-hygroscopic resin to obtain composite particles;

[0112] S3. The composite particles are placed at room temperature and RH of 65% for 1.5 hours, and then dried at 110°C for 4 hours. Part of the sepiolite powder will fall off the composite particles after drying. The fallen sepiolite powder is removed by sieving to obtain a desiccant; wherein the weight ratio of the self-hygroscopic resin to the sepiolite powder in the finished desiccant particles is 1:1.

[0113] Application Example 2

[0114] A desiccant, the preparation method of which is as follows:

[0115] S1. Soak 1 kg of the autonomous hygroscopic resin obtained in Example 1 in deionized water for 2 h to allow the autonomous hygroscopic resin to absorb water and swell:

[0116] S2. After the swelling of the self-hygroscopic resin, the surface moisture was dried and blended with 40kg of sepiolite powder, and the blending time was 5min, so that the sepiolite powder was wrapped in the surface of the self-hygroscopic resin to obtain composite particles;

[0117] S3. The composite particles are placed at room temperature and RH of 65% for 2 hours, and then dried at 110°C for 4 hours. Part of the sepiolite powder will fall off the composite particles after drying. The fallen sepiolite powder is removed by screening to obtain a desiccant; wherein the weight ratio of the self-hygroscopic resin to the sepiolite powder in the finished desiccant particles is 1:1.5.

[0118] Application Example 3

[0119] A desiccant, the preparation method of which is as follows:

[0120] S1. Soak 1 kg of the autonomous hygroscopic resin obtained in Example 1 in deionized water for 2 h to allow the autonomous hygroscopic resin to absorb water and swell:

[0121] S2. After the swelling of the self-hygroscopic resin, the surface moisture was dried and blended with 50kg of sepiolite powder, and the blending time was 5min, so that the sepiolite powder was wrapped in the surface of the self-hygroscopic resin to obtain composite particles;

[0122] S3. The composite particles are placed at room temperature and RH of 65% for 2.5 hours, and then dried at 110°C for 4 hours. Part of the sepiolite powder will fall off the composite particles after drying. The fallen sepiolite powder is removed by screening to obtain a desiccant; wherein the weight ratio of the self-hygroscopic resin to the sepiolite powder in the finished desiccant particles is 1:2.

[0123] Application Example 4

[0124] A desiccant, the preparation method of which is as follows:

[0125] S1. Soak 1 kg of the autonomous hygroscopic resin obtained in Example 1 in deionized water for 2 h to allow the autonomous hygroscopic resin to absorb water and swell:

[0126] S2. After the swelling of the self-hygroscopic resin, the surface moisture was dried and blended with 60kg of sepiolite powder, and the blending time was 5min, so that the sepiolite powder was wrapped in the surface of the self-hygroscopic resin to obtain composite particles;

[0127] S3. The composite particles are placed at room temperature and RH of 65% for 2.5 hours, and then dried at 110°C for 4 hours. Part of the sepiolite powder will fall off the composite particles after drying. The fallen sepiolite powder is removed by screening to obtain a desiccant; wherein the weight ratio of the self-hygroscopic resin to the sepiolite powder in the finished desiccant particles is 1:4.

[0128] Application Example 5-21

[0129] Different from Application Example 2, the autonomous hygroscopic resins in Application Examples 5-21 are from Examples 2-18, respectively.

[0130] Application Examples 22-24

[0131] The difference from Application Example 19 is that in Application Examples 22-24, the sepiolite powder is replaced with an equal amount of modified sepiolite powder from Preparation Examples 1-3, respectively, and the rest is the same as Application Example 19.

[0132] Application Comparative Examples 1-5

[0133] The difference from Application Example 1 is that the autonomous hygroscopic resins in Application Comparative Examples 1-5 are from Comparative Examples 1-5 respectively.

[0134] The moisture absorption rate and average moisture absorption rate of the desiccant in Application Examples 1-24 and Comparative Examples 1-5 were measured. The moisture absorption rate was determined by referring to the moisture absorption rate detection method of the resin. Then, the average moisture absorption rate was calculated. The average moisture absorption rate = (final weight - initial weight) / (initial weight·moisture absorption time). The average moisture absorption rate was expressed in mg / (g·min). The test results are shown in Table 6.

[0135] Table 6 Performance test results of different desiccants

[0136]

[0137]

[0138] Combining Application Examples 1-24 with Embodiments 1-18, and combining Tables 4 and 5, it can be seen that, compared with simply using resin as a desiccant, the moisture absorption rate can be improved by wrapping sepiolite powder outside the resin to prepare a desiccant. This may be because wrapping sepiolite powder outside the resin can increase the roughness of the resin surface and increase the specific surface area of ​​the resin, thereby increasing the contact area between the desiccant and the moisture in the air and improving the moisture absorption performance of the desiccant.

[0139] Combining Application Example 19 with Application Examples 22-24 and Table 5, it can be seen that the moisture absorption rate of the desiccant in Application Examples 22-24 is higher than that in Application Example 19. This may be because the modification of the sepiolite powder by encapsulating with silane coupling agent and sodium polyacrylate improves the dispersion performance of the sepiolite powder, prevents flocculation and agglomeration between the sepiolite powder particles, and makes the sepiolite powder evenly distributed on the resin surface, which is conducive to improving the moisture absorption effect of the resin. Moreover, the moisture absorption rate of the desiccant in Application Example 22 is higher than that in Application Examples 23-24. This may be because when the silane coupling agent and sodium acrylate are mixed to modify the sepiolite powder, the silane coupling agent and sodium acrylate have a synergistic effect, which can further improve the dispersion performance of the sepiolite powder compared to the use of silane coupling agent or sodium acrylate alone.

[0140] Combining Application Example 2, Application Example 9 and Application Comparative Examples 1-5, and combining with Table 5, it can be seen that the moisture absorption rate of the desiccant in Application Example 2 and Application Example 9 is higher, which indicates that the desiccant prepared by compounding the resin prepared in this application with sepiolite powder has a better moisture absorption effect.

[0141] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A desiccant, characterized in that: The desiccant comprises an autonomous hygroscopic resin and sepiolite powder, wherein the weight ratio of the autonomous hygroscopic resin to the sepiolite powder is 1:(1-2); the preparation method of the autonomous hygroscopic resin is as follows: The acrylamide, the metal salt solution, the initiator and the cross-linking agent are uniformly mixed, and a polymerization reaction is carried out under stirring to obtain a reactant, and the reactant is dried to obtain a self-hygroscopic resin; The metal salt solution is an alkali metal salt solution or an alkaline earth metal salt solution; The alkaline earth metal salt solution is a calcium chloride solution, the molar ratio of acrylamide to calcium chloride is 1:(1-3.5), and the concentration of the calcium chloride solution is 1-5 mol / L; The alkali metal salt solution is a lithium chloride solution, the molar ratio of acrylamide to lithium chloride is 1:(1-3), and the concentration of the lithium chloride solution is 1-7 mol / L; The sepiolite powder is modified sepiolite powder, and the modification method thereof is as follows: The sepiolite powder was modified by using a mixed solution of silane coupling agent and sodium polyacrylate.

2. The desiccant according to claim 1, characterized in that: The temperature of the drying operation is 70-80°C and the drying time is 23-25h.

3. The desiccant according to claim 1, characterized in that: The initiator is potassium persulfate, and the cross-linking agent is NN methylene bisacrylamide.

4. A method for preparing the desiccant according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Soak the self-hygroscopic resin in deionized water to absorb water and swell: S2. After the swelled self-hygroscopic resin is wiped dry and the surface moisture is blended with the modified sepiolite powder, so that the modified sepiolite powder is wrapped in the surface of the self-hygroscopic resin to obtain composite particles; S3. The composite particles are placed in an environment of 23±2°C and RH less than 70% for 1.5-2.5 hours, and then dried, and the sepiolite powder falling off the surface of the composite particles is sieved out to obtain a desiccant.

Citation Information

Patent Citations

  • Drying agent

    JP2002336638A